Evaluation of Fibroblasts Adhesion and Proliferation on Alginate-Gelatin Crosslinked Hydrogel - Sarker, Bapi; Singh, Raminder; Silva, Raquel; Roether, Judith A.; Kaschta, Joachim; Detsch, Rainer; Schubert, Dirk W.; Cicha, Iwona; Boccaccini, Aldo R. (PLOS ONE, 2014)
Due to the relatively poor cell-material interaction of alginate hydrogel, alginate-gelatin crosslinked (ADA-GEL) hydrogel was synthesized through covalent crosslinking of alginate di-aldehyde (ADA) with gelatin that supported cell attachment, spreading and proliferation. This study highlights the evaluation of the physico-chemical properties of synthesized ADA-GEL hydrogels of different compositions compared to alginate in the form of films. Moreover, in vitro cell-material interaction on ADA-GEL hydrogels of different compositions compared to alginate was investigated by using normal human dermal fibroblasts. Viability, attachment, spreading and proliferation of fibroblasts were significantly increased on ADA-GEL hydrogels compared to alginate. Moreover, in vitro cytocompatibility of ADA-GEL hydrogels was found to be increased with increasing gelatin content. These findings indicate that ADA-GEL hydrogel is a promising material for the biomedical applications in tissue-engineering and regeneration.